A Newly Isolated Streptomyces sp. YYS-7 With a Broad-Spectrum Antifungal Activity Improves the Banana Plant Resistance to Fusarium oxysporum f. sp. cubense Tropical Race 4 - Wei, Yuanyuan; Zhao, Yankun; Zhou, Dengbo; Qi, Dengfeng; Li, Kai; Tang, Wen; Chen, Yufeng; Jing, Tao; Zang, Xiaoping; Xie, Jianghui; Wang, Wei (Frontiers in Microbiology, 2020)
Fusarium wilt of banana caused by Fusarium oxyspoum f. sp. cubense (Foc) is one of the most destructive diseases, severely limiting the development of banana industry. Especially, Foc tropical race 4 (Foc TR4) can infect and destroy almost all banana cultivars. Until now, there is still a lack of an effective method for controlling fusarium wilt. A biocontrol strategy using actinobacterium is considered as a promising method for management of disease and pest. In this study, 229 Actinobacteria were isolated from rhizosphere soil samples of a primitive ecological mountain. An actinobacterium strain marked with YYS-7 exhibited a high antifungal activity against Foc TR4. Combining the physiological and biochemical characteristics as well as alignment of the 16S rRNA sequence, the strain YYS-7 was assigned to Streptomyces sp. The crude extracts of Streptomyces sp.YYS-7 obviously inhibited the mycelial growth of Foc TR4. The cell integrity and ultrastructure were seriously destroyed. In addition, Streptomyces sp. YYS-7 and crude extracts also showed a broad-spectrum antifungal activity against the selected seven phytopathogenic fungi. A gas chromatography-mass spectrometry (GC-MS) was used to predict the antifungal metabolites. A total of eleven different compounds were identified, including phenolic compounds, hydrocarbons, esters and acids. In the pot experiment, the crude extracts can significantly improve the banana plant’s resistance to Foc TR4. Hence, Streptomyces sp.YYS-7 will be a potential biocontrol agent for the biofertilizer exploitation and the discovery of new bioactive substances.